PERAN KEPEMIMPINAN KIAI HAJI HASAN EFFENDI DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI PONDOK PESANTREN AL-KAUTSAR SATUI TANAH BUMBU - Patmawati, Laila (Universitas Lambung Mangkurat, 2015)
The aim of this study was to describe the leadership style ofÂ Kiai.H. Hasan Effendi and tried to portray his role in improving the quality of education in Pondok Pesantren Al-Kautsar Satui, Tanah Bumbu. The approach in this study was qualitative. The first data were in the form of data records through observation, interviews supporting data, and the data from the archives ofÂ Pondok Pesantren Al-Kautsar Satui. Next, the data in the form of tape from relevant parties. To facilitate the discussion of the problem, the data from recorded interviews were later transcribed into writing. The next step was to test the validity of such data by triangulation method. Triangulation used include triangulation of sources, techniques, and time. This study found that Kiai H. Hasan Effendi in boarding school Al-Kautsar is a leader who was appointed directly by the boarding school founder Habib Saleh bin Mukhtar Al-Iderus. Her leadership style tends paternalistic style, the leadership of the grandfatherly. He has a role as an educator who guides Ustad/Ustazah to have better maturity in the sense of being more responsible. In this case, he has a role as a motivator, manager, administrator, supervisor, leader, and innovator.Keywords: leadership style, leadership role quality education, pesantren education.